Characterization of acaricide resistance in tick isolates collected from Rajasthan, India - KUMAR, SACHIN; SHARMA, ANIL KUMAR; NAGAR, GAURAV; RAWAT, SUMER SINGH; TIWARI, SHASHI SANKAR; KUMAR, RINESH; DHAKAD, M L; SHARMA, RAKESH KUMAR; SAXANA, RAKESH KUMAR; MEHRANIYA, RANJEET SINGH; SINGH, RAM SAJIWAN; JAIN, D K; et al. (The Indian Journal of Animal Sciences, 2016)
Rhipicephalus (Boophilus) microplus and Hyalomma anatolicum are the most common tick species infesting milk and meat producing animals throughout the country. The present study was conducted to evaluate the acaricide resistance status of the tick species to deltamethrin, cypermethrin, diazinon collected from 10 districts of Rajasthan. Characterization of resistance was carried out by adult immersion test (AIT) and larval packet test (LPT). In case of (B.) microplus resistance to deltamethrin at level I (RF = 2.5 – 4.9) in 02 isolates, at level II in 03 isolates (RF = 5.4 – 11.5) and level IV in 02 isolates (RF = 48.1 – 95.7) was detected. The resistance to cypermethrin was detected in 08 isolates of which resistance at level I in 03 isolates (RF = 2.7 - 4.58) and at level II in 05 isolates (RF = 8.05 – 16.2). Diazinon resistance was detected at level II in 06 isolates (RF = 5.8 –22.8), at level III in 01 isolates (RF = 39.0) and level IV in 02 isolates (RF = 65.9 – 66.0). While in case of H. anatolicum, the resistance to deltamethrin at level I (RF = 1.79 –2.52) in 03 isolates, to cypermethrin in 03 isolates (RF= 2.0 - 3.95) and to diazinon at level I in 03 isolates (RF = 1.32 –2.18) out of eleven isolates was detected.        A significant correlation between esterase enzyme ratio and resistant factor of tick isolates was observed with correlation coefficient (r) in α- and ß-esterase activity. The coefficient of determination (R2) for α- and ß-esterase activity indicated that 55.9 and 50.5% data points of R.(B.) microplus isolates and 66.7 and 47.2% data points of H. anatolicum isolates were very close to the correlation lines.      Analysis of sequence data of 3 targeted positions of the sodium channel gene detected a cytosine (C) to adenine (A) nucleotide substitution (CTC to ATC) at position 190 in domain II S4–5 linker region of para-sodium channel gene in 3 isolates and in reference deltamethrin resistant IVRI-IV line.     The western dry region and central plateau hills region revealed higher density of resistant ticks where intensive crossbred cattle population are reared and synthetic pyrethroids and organophosphate compounds are commonly used. The data shows an urgent need of revisiting the tick control strategy implemented through concerned government/non-government agencies.